The Last Patient - Pi, Diana J. (Ars Medica, 2019)
Last message and you're done. Twenty years as a GP in a county hospital, this isn’t the career ending you’ve envisioned. But it is what it is. The night maintenance man has just arrived, salting the air with the smell of lemon antiseptic and longing music from a faraway land. All these years you passed each other at the hallway, you’ve never bothered to find out his name. The lone message reads, Urgent, Dr. Pi, please instruct. And it's dated yesterday. You know what the ER wants from you, and you’ve waited and waited and it’s all too late now. They know you fuck up.